The Effect of Vitamin D3 on the Alignment of Mandibular Anterior Teeth: A Randomized Controlled Clinical Trial - Ali Al-Attar; Mushriq Abid (International Journal of Dentistry)
Objectives. To investigate the effect of vitamin D3 level on the alignment of mandibular anterior teeth in adults and explore the associated root resorption and pain perception. Trial Design. Multicentre, double blinded randomized clinical trial. Subjects and Methods. Adult patients aged 18–30 years, with moderate mandibular incisor crowding [Little’s Irregularity index (LII) 3–6 mm], needing nonextraction treatment with fixed orthodontic appliance, were randomly allocated into two groups with 1 : 1 allocation ratio. In the 1st group (normal vitamin D3 level group [ND3G]), vitamin D level was measured and corrected to normal before starting orthodontic treatment, while in the 2nd group [control group (CG)] the vitamin D level was kept unknown until completion of the alignment phase. Outcome measures included mandibular incisor crowding using LII, orthodontically induced root resorption (OIRR), and pain perception. Independent sample t-test was used to compare the duration of treatment, the effectiveness of alignment, and OIRR between groups, while differences in pain perception were analysed by Mann–Whitney U-test (P<0.05). Results. Out of 87 patients recruited from four centres, 33 patients were randomly allocated into two groups (17 patients to ND3G and 16 patients to CG). Time elapsed for the complete alignment of the mandibular incisor crowding was one month shorter in ND3G (23.532% faster), and the improvement percentage was significantly higher in all periods when compared to the CG. The amount of OIRR was not significantly different between groups; however, pain during the first three days of alignment was significantly less in ND3G. Conclusions. Having optimal vitamin D3 level reduced the alignment time and pain associated with orthodontic treatment, but it had no role in reducing OIRR. Registration. The trial was registered with ClinicalTrials.gov on 12th April 2021 (registration number: NCT04837781).